(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Despite noticeable advancements in the social status of villages across Haryana, significant challenges persist for a substantial portion of the population, particularly in accessing higher education and essential amenities. While the government has made strides in extending basic facilities to rural areas, many residents still face obstacles in obtaining adequate healthcare, education, and sanitation services. To better understand these ongoing issues, a detailed case study was conducted in Baliana village, located in the Rohtak District. This study aimed to evaluate various indicators of education levels and socio-economic statuses within the rural Households. Key parameters examined included household amenities, educational attainment, occupational levels, and income levels. The objective was to analyze the village's socio-economic landscape and educational dynamics comprehensively. The research relied on primary data collected from 85 households, encompassing a total of 260 respondents. Through this data, the study sought to gain a nuanced understanding of the Households’s access to fundamental resources and the overall impact of infrastructural improvements on their daily lives.